Chemical Composition and Crystal Morphology of Epicuticular Wax in Mature Fruits of 35 Pear (Pyrus spp.) Cultivars - Wu, Xiao; Yin, Hao; Shi, Zebin; Chen, Yangyang; Qi, Kaijie; Qiao, Xin; Wang, Guoming; Cao, Peng; Zhang, Shaoling (Frontiers in Plant Science, 2018)
An evaluation of fruit wax components will provide us with valuable information for pear breeding and enhancing fruit quality. Here, we dissected the epicuticular wax concentration, composition and structure of mature fruits from 35 pear cultivars belonging to five different species and hybrid interspecies. A total of 146 epicuticular wax compounds were detected, and the wax composition and concentration varied dramatically among species, with the highest level of 1.53 mg/cm2 in Pyrus communis and the lowest level of 0.62 mg/cm2 in Pyrus pyrifolia. Field emission scanning electron microscopy (FESEM) analysis showed amorphous structures of the epicuticular wax crystals of different pear cultivars. Cluster analysis revealed that the Pyrus bretschneideri cultivars were grouped much closer to Pyrus pyrifolia and Pyrus ussuriensis, and the Pyrus sinkiangensis cultivars were clustered into a distant group. Based on the principal component analysis (PCA), the cultivars could be divided into three groups and five groups according to seven main classes of epicuticular wax compounds and 146 wax compounds, respectively.